Analysis of Family Economic Factors on Students' Learning Interest Using the C4.5 Algorithm - Rahayu, Dian; Solikhun, Solikhun; Sormin, Rizky Kairunnisa (JOMLAI: Journal of Machine Learning and Artificial Intelligence, 2023)
This study aims to analyze the influence of family economic factors on the learning interest of students at SMA Negeri 2 Pematangsiantar using the C4.5 algorithm. The C4.5 method is employed to identify the relationship between family economic variables and students' learning interest. The research is conducted at SMA Negeri 2 Pematangsiantar, involving students as the main respondents. Data is collected through a questionnaire covering family economic variables and the level of students' learning interest. Data analysis using the C4.5 algorithm assists in identifying family economic factors that significantly affect students' learning interest. The study's results are expected to provide a deeper understanding of the impact of family economic factors on student learning motivation in the high school environment. This research contributes to the education literature and offers insights for educators, parents, and education stakeholders to enhance support for students with diverse family economic backgrounds. The implications of these findings can aid in designing more inclusive education policies and supporting academic growth for high school students.